(untitled) (diségno, 2023)
The contribution investigates the role of the bird’s eye view in perception and thus in the design of buildings and the city. The development of satellite technologies and their use on a large scale is considered a threshold towards a new way of conceiving architecture. In fact, the web allows virtual trips around the world and, the first interface with the city and its architecture is often the view offered by satellite image software. Their wide use, also as navigation tools, has changed the way of relating to the city. Whereas once the first interface between the building and the visitor was the façade, today the roof is often the first visible element. This change has also had an impact on the design of new buildings. For example, technical rooms are increasingly being hidden by roofs, and replaced by garden roofs, which are more attractive for viewing from above. Similarly, large-scale urban interventions, from the expansion plans of artificial islands in gulf countries to the mammoth buildings erected in deserts, follow geometries that are easily recognizable from above. They often use formal expedients –symmetrical shapes, bright colors, large logos– already in use in airport design, conceived to be seen from the privileged height of an aircraft. The democratization of the processes of viewing from above has led to a rethinking of the processes of communicating architecture, which no longer interfaces with the limited audience of flesh-and-blood visitors, but with the broader audience of people connected to the web.